Detection Of Point Mutation (Pro30Leu) In Exon 1 Of The 21-Hydroxylase Gene(Cyp21) In Patient With Congenital Adrenal Hyperplasia Using Digoxygenin System . - Muhamad, Y.K.; Fuziah, M.Z.; Rus Anida, A.; Sidek, M.Ros; Ramli, S.F.; Adam, N.; Isa, M.N. (2001)

(untitled)
Congenital adrenal hyperplasia IS an autosomal recessive disease with a wide range of clinical manifestations.